PENGEMBANGAN MEDIA VIDEO ANIMASI BERBASIS KEARIFAN LOKAL RIAU PADA MATERI IDENTITAS MASYARAKAT DI LINGKUNGAN TEMPAT TINGGALKU KELAS IV SEKOLAH DASAR - Yuliska, Adilla; Ramadan, Zaka Hadikusuma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low interest and understanding of students in the subject of Pancasila Education, particularly on the topic of community identity in their living environment, due to the limited use of learning media that still focused on textbooks and pictures. This study aimed to develop an animated video learning media based on Riau local wisdom that is feasible for use in the learning process of fourth-grade students at elementary school. This research employed the Research and Development (R&D) method using the 4D model, which consists of Define, Design, Development, and Disseminate stages. However, the study was limited only to the Development stage. Data collection techniques included interviews, questionnaires, and documentation. The research subjects consisted of six validators, namely two material experts, two language experts, and two media experts. The results showed that the animated video media based on Riau local wisdom obtained an overall average percentage score of 87.52% and was categorized as “very valid.” The validation results for the material aspect reached 88.33%, the language aspect reached 85.16%, and the media aspect reached 89.06%. Based on these findings, the animated video media based on Riau local wisdom was declared feasible for use in the learning process and was able to create a more engaging, contextual, and easily understood learning experience for students.